Cover Image, Volume 29, Issue 12. Issue 12 (20th November 2019) - Myrum, Craig; Rossi, Sharyn L.; Perez, Evelyn J.; Rapp, Peter R.
Abstract : Cover legend: This cover image is based on the Research Article Cortical network dynamics are coupled with cognitive aging in rats by Craig Myrum et al, https://doi.org/10.1002/hipo.23130 . Cover Image © National Institutes of Health Images.